Integrated curriculum success and challenges: a review of the experience of the International Islamic School Malaysia (IISM) - Merah, Souad; Tahraoui, Ramdane (2014)

(untitled)
Education is one of the most important aspects of the human life, perhaps the most influential social system that man was able to create. The future of any nation rests on its educational system. In most western societies, education turned into a driving force that contributes to nation building, by providing individuals with necessary skills and knowledge, and prepares them to enter job markets, compete for better opportunities, and meet the demands of life in the modern age. Education in Islam however, has much wider spectrum. Every positive action a Muslim does or seeks including seeking knowledge is regarded as an act of worship (ibadah), which brings God’s blessing and deserves reward. Another dimension of education in Islam is the fact that it is considered as a mean to protect the faith and its tenets, as well as to preserve the tradition and the Islamic way of life. The launching of Islamic education in a very early stage, simultaneously with efforts of the Islamic call (da’wah), -which, in its essence seeks to spread the principles of faith and gain Allah’s favors by living according to his commands in this world and preparing for the day after- such simultaneousness symbolizes the importance of education, even for the survival of the faith itself. The educational Islamic experience witnessed several periods of tide and ebb. It reached its peak during the medieval ages, with outstanding scientific, intellectual accomplishments, and leading roles, which rendered the Islamic orient as a center for knowledge and innovation. However, primarily political, and intellectual conditions which began to accumulate in the tenth century BC, led to an extreme tide of regression in the Islamic intellectualism and intelligentsia. In contrast Europe was initiating an intensive educational and rational travail of renaissance, pragmatism, scientific exploits, industrialization, and reforms which ultimately revitalized, transformed and reinstated it to its leading role. The new order was culminated by the military European colonial offensive against the Muslim world in the 18th, 19th and 20th centuries. The incapacitation of Muslim role in making of civilization, and relegating their influence, was not because of the western domination solely. In contrast, the domestic intellectual malaise and internal educational decay among Muslims is the prime culprit which allowed such situation to exist. The task shouldered by Muslim educators, academics and activists to rejuvenate Islamic education is complicated and heavy indeed, especially with the decadence, deterioration, and acute illnesses of life conditions in the Muslim world. One major contemporary challenge that needs to be addressed seriously and find remedies to it is the issue of dualism in most of educational systems in the Muslim countries. It is manifested in a form of religious versus secular curriculum. Of course, there were many conflicting views among scholars, decision makers and even parents about the best solution to tackle this issue. Some, driven by philosophical and economic incentives would favor the western secular system, because according to them, it is modern, progressive and highly demanded in the job markets. Others, driven by religious motives rather prefer the traditional Islamic education. For them such system will help to preserve the Islamic identity of the new generation. Between these two conflicting views, a third opinion, which claim balance and moderation calls for the balance between the acquisition of revealed and western sciences in one educational package, in other words, it adopts the approach of teaching an integrated curriculum. Ultimately, many educational institutions and projects in the Muslim world were established based on the concept of integrated curriculum. This paper tries to review the idea of school integrated curriculum through the experience of one leading educational institution in Malaysia, that the International Islamic School Malaysia (IISM). The school which started to operate in 1998 was the result of several years of planning and projection by the international Islamic university Malaysia. After reaching 16 years of operation, and with many phases of success and disappointments, the researchers think that it is a ripe time to conduct this review.